Economic crime, tax evasion and gender: evidence from a developing country = Delincuencia económica, evasión fiscal y género : datos de un país en desarrollo = Crime econômico, evasão fiscal e gênero : evidências de um país em desenvolvimento - Knežević, Goranka (Revista Criminalidad, 2024)
Our attention has been attracted by the proposition that the gender and criminal behaviour of perpetrators of economic and tax crimes in the context of a developing country such as Serbia could be explained by the secondary data set. The data set taken into analysis ascertains whether women are less reported, prosecuted, and convicted than men and what the plausible explanation for that phenomenon is. Before COVID-19, more men were prosecuted and convicted for those crimes, and statistics show that approximately 85 - 90 % of perpetrators of economic crime and tax fraud are men. Although women have less economic power, they show lower criminal behaviour. In the year 2020, which is considered to be the COVID-19 outbreak year, the trend has been the same, but the number of women being prosecuted and convicted for economic crimes more than doubled in Serbia. This is because women are exposed to a huge risk in providing income for their families and supporting their needs forces them to commit economic fraud more than ever before. To further explain factors influencing women’s economic criminality, we compare them with similar countries in the Balkan region (Croatia and Montenegro). When the totals are compared, women show a lower tendency to express criminal behaviour than men. Still, these numbers are higher for economic crime than for other forms of criminality, meaning that the gender gap in economic crime is narrowing. This leads to the recommendation that legal sanctions are not severe enough and that some changes in criminal law are needed to prevent both sexes from finding economic and tax fraud to be good alternatives to receive economic benefits.